2018
DOI: 10.1007/s00542-018-4011-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast all-optical ALU operation using a soliton control within the cascaded InGaAsP/InP microring circuits

Abstract: A dark-bright soliton conversion is used to perform the two arithmetic logic unit(ALU) operations namely adder and subtractor operations. The advantage of the system such as power stability, non-dispersion and the dark-bright soliton phase conversion control can be obtained. The input source into the circuit is the bright soliton pulse, with the pulse width of 35 ps, the peak power at 1.55 µm is 1 mW. By using the dark-bright soliton conversion pair, the generated logic bits can be controlled, and the secure b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[10] Lan et al also investigated a non-autonomous generalized AB system, and found that the two short waves and mean flow can appear as the solitary waves. [11] These various phenomena undoubtedly illustrate that optical solitons are excellent candidates to realize alloptical switching and routing, [12][13][14][15] which are key technologies for all-optical communication network based on light controlling light. Until now, optical solitons have been studied, which can exist in many kinds of nonlinear optical materials such as Kerr medium, [16,17] photorefractive (PR) crystal, [18][19][20][21] and liquid crystal.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Lan et al also investigated a non-autonomous generalized AB system, and found that the two short waves and mean flow can appear as the solitary waves. [11] These various phenomena undoubtedly illustrate that optical solitons are excellent candidates to realize alloptical switching and routing, [12][13][14][15] which are key technologies for all-optical communication network based on light controlling light. Until now, optical solitons have been studied, which can exist in many kinds of nonlinear optical materials such as Kerr medium, [16,17] photorefractive (PR) crystal, [18][19][20][21] and liquid crystal.…”
Section: Introductionmentioning
confidence: 99%